2014
DOI: 10.1016/j.vetpar.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficacy of orally administered afoxolaner against Rhipicephalus sanguineus sensu lato

Abstract: Two studies were conducted to confirm that a single oral dose of the novel insecticide/acaricide afoxolaner is efficacious against existing infestations of Rhipicephalus sanguineus sensu lato in dogs and can control re-infestation for up to 35 days. Each study utilized 16 purpose bred adult dogs using a controlled randomized block design. One or two days prior to treatment, all dogs were infested with 50 unfed adult ticks. On Day 0 one group was treated with an oral chewable formulation of afoxolaner at a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…Similarly, a single dose of NexGard®, reduced populations of C. felis by 100% within 24 h and blocked egg production by >99% over 36 days [22, 23]; additional re-treatment at days 28–30, achieved total flea control by 60 days [24]. Other studies of single doses of NexGard® report complete elimination of pre-existing Dermacentor reticulatus, D. variabilis and Ixodes ricinus infestations and sustained efficacy of >96% one month later [25, 26] and significant reductions in R. sanguineus and Haemaphysalis longicornis by >96% after 35 days [27] and 92% after 30 days [28], respectively; maximum plasma levels are observed at 2–6 h and mean half-life is 15.5 days [17]. A direct comparison of immediate efficacy of Bravecto® and NexGard® against R. sanguineus demonstrated that onset of activity was 4 h and 8 h, respectively, and 100% mortality was achieved within 12 h and 48 h, respectively [21].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a single dose of NexGard®, reduced populations of C. felis by 100% within 24 h and blocked egg production by >99% over 36 days [22, 23]; additional re-treatment at days 28–30, achieved total flea control by 60 days [24]. Other studies of single doses of NexGard® report complete elimination of pre-existing Dermacentor reticulatus, D. variabilis and Ixodes ricinus infestations and sustained efficacy of >96% one month later [25, 26] and significant reductions in R. sanguineus and Haemaphysalis longicornis by >96% after 35 days [27] and 92% after 30 days [28], respectively; maximum plasma levels are observed at 2–6 h and mean half-life is 15.5 days [17]. A direct comparison of immediate efficacy of Bravecto® and NexGard® against R. sanguineus demonstrated that onset of activity was 4 h and 8 h, respectively, and 100% mortality was achieved within 12 h and 48 h, respectively [21].…”
Section: Discussionmentioning
confidence: 99%
“…Afoxolaner is a highly effective ectoparasiticide used against flea and tick infestations in dogs (Dumont et al ., ,b; Hunter et al ., ; Kondo et al ., ; Kunkle et al ., ,b; Mitchell et al ., ,b). The high potency against fleas and ticks is a hallmark of isoxazoline parasiticides (Ozoe et al ., ; Woods et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in research for ectoparasite control have brought a new oral therapeutic drug forward for clinical usage. NexGard ® (Merial Inc., Duluth, GA, USA; a beef‐flavored chewable for dogs) contains afoxolaner (a compound from a new structurally unique isoxazoline class), which acts as a novel and specific blocker of insect ligand‐gated chloride ion channels (Shoop et al ., ) and is thus effective against both fleas and ticks (Dumont et al ., ,b Hunter et al ., ; Kondo et al ., Kunkle et al ., ,b Mitchell et al ., ,b). Combining afoxolaner with milbemycin oxime in a beef‐flavored chewable allows owners to administer one product per month instead of several because milbemycin oxime extends the spectrum of activity to the treatment of intestinal nematodes and prevention of heartworm disease ( Dirofilaria immitis ).…”
Section: Introductionmentioning
confidence: 99%
“…(Paper received 30 April 2016; accepted for publication 23 September 2016) INTRODUCTION Advances in research for ectoparasite control have brought a new oral therapeutic drug forward for clinical usage. NexGard â (Merial Inc., Duluth, GA, USA; a beef-flavored chewable for dogs) contains afoxolaner (a compound from a new structurally unique isoxazoline class), which acts as a novel and specific blocker of insect ligand-gated chloride ion channels (Shoop et al, 2014) and is thus effective against both fleas and ticks ,b Hunter et al, 2014Kondo et al, 2014Kunkle et al, 2014a,b Mitchell et al, 2014a.…”
mentioning
confidence: 99%